2017
DOI: 10.4103/ajm.ajm_204_16
|View full text |Cite
|
Sign up to set email alerts
|

An online academic writing and publishing skills course: Help Syrians find their voice

Abstract: Purpose: A group of Arab-American physicians and researchers in the United States organized a blended online course in academic writing and publishing in medicine targeting medical students and physicians in war-torn Syria. This was an effort to address one of the reasons behind the poor quantity and quality of scientific research papers in Syria and the Arab region. In this paper, we report on the design, conduct, and outcome of this course and attempt to evaluate its effectiveness. Methods: The educational i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In the GCAs, innovation was a key theme which was mainly led by students and trainees. This included trialling small scale initiatives in teletraining, peer-led teaching and training the trainers, which were focused on topics such as EBM and academic writing and BLS courses27 28 36–38 In addition to calls from the academic staff for community-based learning,39 conflict-focused curriculum in mental health40–42 and trials of bilingual teaching approaches in medical schools 43–45…”
Section: Resultsmentioning
confidence: 99%
“…In the GCAs, innovation was a key theme which was mainly led by students and trainees. This included trialling small scale initiatives in teletraining, peer-led teaching and training the trainers, which were focused on topics such as EBM and academic writing and BLS courses27 28 36–38 In addition to calls from the academic staff for community-based learning,39 conflict-focused curriculum in mental health40–42 and trials of bilingual teaching approaches in medical schools 43–45…”
Section: Resultsmentioning
confidence: 99%
“…In Syrian, they were suggested as an attainable alternative to address the shortcomings of the research curriculum (10,16). Previous reports assessing individual interventions that targeted research skills including EBM and academic writing in Syria highlighted the knowledge-enhancing effects of their workshops (11,13,14,26), or at least improvement limited to attendees' confidence (27), or perceived skills (15). Additionally, a recent crosssectional study on Syrian residents suggested that attending more trainings on medical research correlates with better practices of EBM (28).…”
Section: Discussionmentioning
confidence: 99%
“…The extracurricular interventions targeting medical research paucity in Syria have proven successful in helping Syrian early-career medical researchers to find their voice (27). Regardless of the dreadful circumstances of war, these workshops increased research attitudes, knowledge, skills, and productivity, and facilitated engagement in the research community.…”
Section: Discussionmentioning
confidence: 99%
“…29 Online workshops can also provide a more affordable, accessible, and flexible option that still leads to comparable outcomes. 14 30 31 32 33 These educational events should be recorded and published afterward for self-paced learning, which was deemed highly effective, and should cover all aspects of research methodology, academic writing, and biomedical statistics, as training was lacking overall.…”
Section: Discussionmentioning
confidence: 99%